Optimalisasi Perkembangan Anak Usia Dini Melalui Strategi Stimulasi Neurologis: Literature Review - desi ismawati; Sitti Romlah; Sohibul Hajad; Ismawati; mohammad Fahrur Rosi (Jurnal Kajian Anak (J-Sanak), 2026)
The golden age period is a critical phase in early childhood neurological development that significantly determines cognitive, language, motor, and socio-emotional development in later life. However, many parents and early childhood educators still have limited understanding of appropriate neurological stimulation strategies, particularly in regions with limited access to educational information such as Pamekasan. This study aims to review various neurological stimulation strategies to optimize early childhood development. The method used is a literature review by analyzing 12 national and international scientific articles published between 2020-2026 from Google Scholar, DOAJ, and Scopus databases. The findings reveal that social stimulation is the most effective strategy, followed by Brain Gym, multisensory play, read-aloud activities, and papercraft. These results indicate that strategies based on direct interaction and active learning experiences are more effective in supporting children's neurological development compared to individual-based approaches. In addition, multisensory stimulation and creative activities contribute to enhancing neuroplasticity and optimizing brain function. The novelty of this study lies in the comprehensive synthesis of evidence-based neurological stimulation strategies and their relevance in early childhood education and parenting contexts in local communities. This review is expected to serve as a practical reference for early childhood educators and parents in optimizing child development during the golden age period holistically.